Assessment of relevance and effectiveness of community health workforce (CHW) development system in Bangladesh - Talukder, Md Humayun Kabir; Yasmeen, BH Nazma; Nazneen, Rumana; Hossain, Md Zakir; Chowdhury, Ishrat Jahan (Northern International Medical College Journal, 2015)
Background : Community Health Workforce (CHW) development has a rich history in South East Asian Region (SEAR). The first Community Health Unit was established in Sri Lanka in 1926 and then practiced over many of the regional countries like, Thailand, Mayanmar and India. Community Health Workers are in the fore front workforce to bring about change through community health programmes to national levels. In Bangladesh, there are also different categories of health workforce serving in the health care delivery system. Objectives : To assess relevance and effectiveness of community health workforce (CHW) development system in Bangladesh. Methods : This cross sectional study was conducted from 1st November 2010-30th April 2011 by purposive sampling technique. Study population were directors, administrators, principals, teachers of different institutes/ organizations and community health workers working in different corners of Bangladesh. Study places were different divisional towns of Bangladesh. Previously developed questionnaire & checklist were used for the collection of data from the institutes/ organizations by data collectors. These data were edited, processed and was analysed by using SPSS soft ware and a small portion by manually. No strong ethical issues were involved in this activity. Results : Study revealed that all the respondents (100%) are in favour of production of CHW in Bangladesh through formal academic institutional or pre service education (61.4%) .Most of the respondents (56.8%) viewed that there are scopes of utilisation of produced CHW in rural areas and most of the respondents (63.6%) also viewed that terminal/marginalized/underprivileged peoples of hard to reach areas at least can be served by CHW. Regarding the competency of produced CHW few of the respondents (43.2%) viewed positively. Most of the respondents (86.4%) viewed that both govt. & non govt. sectors should produce CHW with a very good coordination and co-operation. Study revealed the institutional capacities or situations about physical facilities, ongoing course, audiovisual aids, library, manpower and assessment procedure. Conclusion : Study revealed that there is strong & logical relevance present for the production of CHW in Bangladesh. So the existing Human Resource for Health (HRH) policy is to be revised & revisited as a time felt need to develop more competent CHW for Bangladesh to serve the marginalized, terminal, people of remote, rural & hard to reach areas. Northern International Medical College Journal Vol.5(2) 2014: 332-335